Fostering Global Citizenship through ESD in Higher Education: A Study of International Student Mobility and Sustainability Awareness - Doris Chasokela (Journal of Education for Sustainable Development Studies, 2024)
This study investigates the intricate relationship between international student mobility and sustainability awareness within the context of higher education, emphasizing the role of Education for Sustainable Development (ESD) in fostering global citizenship. By employing a mixed-methods approach, we surveyed 300 international students from 20 different countries and conducted semi-structured interviews with 20 faculty members across 10 universities. Our findings indicate that international student mobility can significantly enhance sustainability awareness but primarily when ESD principles are effectively integrated into academic curricula. Specifically, students who engaged in programs infused with ESD reported a deeper understanding of sustainability issues and a stronger commitment to global citizenship. The study further reveals that faculty development plays a crucial role in promoting ESD within higher education settings, as instructors equipped with enhanced knowledge and skills in sustainability education are better positioned to transform curricula in meaningful ways. Additionally, institutional policies and frameworks are essential to creating an environment conducive to ESD, ensuring that programs prioritize global citizenship alongside academic performance. By drawing connections between mobility, sustainability awareness, and educational practices, this research underscores the necessity for universities to adopt strategic initiatives and collaborative efforts aimed at embedding sustainability into higher education curricula. In conclusion, this study offers valuable insights for policymakers, educators, and institutions, highlighting the imperative to strengthen ESD practices to cultivate a generation of informed global citizens. The implications of our findings aim to inspire actionable steps toward integrating sustainability within higher education, ultimately promoting a more equitable and sustainable future.